Ultrasound of benign thyroid nodules: A 120 months follow‐up study. (23rd January 2021) - Cappelli, Carlo; Pirola, Ilenia; Gandossi, Elena; Rotondi, Mario; Casella, Claudio; Lombardi, Davide; Agosti, Barbara; Ferlin, Alberto; Castellano, Maurizio
Abstract: Objective: Some evidence suggests that most benign nodules exhibit no significant size increase during 5 years of follow‐up, although conflicting results have emerged. The aim of the present study is to evaluate the frequency and the magnitude of growth in benign nodules during 120 months of follow‐up. Design: We reviewed the medical and imaging records of patients who were submitted to ultrasound‐guided FNA of thyroid nodules at our hospital from January 2007 to March 2009. We selected only patients with benign nodules who underwent annual ultrasound evaluation in our Department. Results: Among 966 selected patients, 289 were lost during follow‐up, meaning that the total number of patients analysed was 677 (474 women and 203 men), with a mean age of 45.6 (16–71) years. In 559/677 patients (82.7%), the size of the nodule remained stable during follow‐up; 42 (6.2%) patients experienced spontaneous nodule shrinkage, and 75 (11.1%) patients showed nodule growth. Patients with or without nodule growth during follow‐up were superimposable at baseline for age, gender, TSH values, number of patients on levothyroxine treatment and nodule characteristics. All baseline variables in predicting nodular growth were entered to an adjusted multivariate logistic regression model. None of the parameters taken into account was associated with nodular growth. Conclusions: In conclusion, the majority of benign nodules remained stable over the period of monitoring. On the basis of our experience, we recommend ultrasound examination at a distance of 2 and 5 years following cytological evaluation, then every 4–5 years from then on.